Occurrence of enteroviruses in community swimming pools. - Keswick, B H (1981)
Municipal swimming pools and wading pools were examined for the presence of human enteric viruses using a portable virus concentrator at the site to concentrate viruses from 100-gallon to 500-gallon samples. Ten of 14 samples contained viruses; three of these were positive for virus in the presence of residual free chlorine. Enteroviruses were isolated from two pools which exceeded the 0.4 ppm free residual chlorine standard. This study appears to be supportive of recent evidence that indicates a higher incidence of enterovirus infection among bathers. All seven wading pool samples contained virus. Coxsackieviruses B3 and B4, poliovirus 1, and echovirus 7 were isolated. Total coliform bacteria were not adequate indicators of the presence of virus, as six of the samples were positive for virus but negative for coliforms. Total plate counts appeared to provide a better indication of the sanitary quality of the pool water, but viruses could still be detected in samples that met currently recommended bacterial levels. It is possible that swimming and wading pools may serve as a means of transmission of enteroviral disease, especially in children, during summer months.